Adalimumab Modulates Angiogenesis in Psoriatic Skin. (May 2013) - Campanati, A.; Moroncini, G.; Ganzetti, G.; Pozniak, K.N.; Goteri, G.; Giuliano, A.; Martina, E.; Liberati, G.; Ricotti, F.; Gabrielli, A.; Offidani, A.
Angiogenesis plays a key role in the pathogenesis of psoriasis. New blood vessel formation occurs early during plaque lesion development in psoriatic skin, and sometimes precedes disease recurrence. TNF-α, a well established mediator of inflammation in psoriasis, up-regulates the transcription of several pro-angiogenic chemokines that are over-expressed in psoriatic skin and serum, promoting microvascular modifications in psoriatic plaque. Adalimumab is a fully human monoclonal antibody that blocks the interaction between TNF-α and its cell surface receptor, thus inhibiting the TNF-α dependent inflammatory cascade. The aims of this study were to investigate several angiogenic parameters involved in the pathogenesis of psoriasis, and to evaluate the ability of adalimumab to modulate them. Fifteen patients affected by psoriasis received Adalimumab 40 mg EOW for twelve weeks and were evaluated at baseline (T0 ) and after treatment (T12 ) for the following parameters: i) new blood vessels formation in lesional skin assessed by intra-vital video-capillaroscopy analysis (IVCP) and histology; ii) VEGF and Factor VIII expression in lesional skin detected by immunohistochemistry; iii) serological levels of several angiogenic chemokines detected by luminex assay. At baseline, newly formed capillaries in psoriatic plaque correlated with skin expression of VEGF and factor VIII and with serum levels of angiopoietin-2, IL-8, PDGF-BB, VEGF, but not with serum levels of follistatin, TNF-α, G-CSF, HGF, FGF, PECAM, IFN-γ, and TGF-α. All patients responded to adalimumab, reached PASI 50, and 70% achieved PASI 75 after twelve weeks of treatment. Although adalimumab administration for twelve weeks caused a dramatic decrease of new blood vessel formation, confirmed by IVCP (p<0.05), histology and immunohistochemical (p<0.05) analysis, we did not observe a parallel significant reduction of angiogenic chemokines in the serum. However, a positive correlation between the density of newly formed blood vessels in lesional skin and the serum levels of angiopoietin-2, IL-8, PDGF-BB, and VEGF, was still persisting after treatment.